2021
DOI: 10.18231/j.ijogr.2021.016
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of incidence of Aerobic vaginitis in women presenting with symptoms of vaginitis

Abstract: Vaginitis is found to be quite common among women who present in Gynecology OPD. Aerobic vaginitis is one of the causes of vaginitis which is typically marked by either an increased inflammatory response or by prominent signs of epithelial atrophy or both. The main aim of the study was to analyze the signs, symptoms and laboratory investigations among women presenting with symptoms of vaginitis. The study consisted of 155 cases of women presenting with symptoms of vaginitis. Brief general, systemic and detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sangeetha K. T. et al in 2015 observed that the most common aerobic bacterial pathogens associated with vaginitis isolated from women patients of reproductive age were E. faecalis (32.26%), followed by E. coli (25.8%), S. aureus (19.35%) and β-hemolytic streptococci (9.68%) [ 7 ]. In contrast, in a recent paper Vidyasagar V. (2021) identified, in women diagnosed with aerobic vaginitis (29–35 years), coagulase-negative Staphylococci growth in 50% cases, and in 25% Streptococci and Klebsiella [ 8 ]. S. aureus was the most abundant isolated pathogen for Nahar D et al (41.07%), Tansarli et al (41.7%) and Zarbo et al (27.9%) [ 12 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sangeetha K. T. et al in 2015 observed that the most common aerobic bacterial pathogens associated with vaginitis isolated from women patients of reproductive age were E. faecalis (32.26%), followed by E. coli (25.8%), S. aureus (19.35%) and β-hemolytic streptococci (9.68%) [ 7 ]. In contrast, in a recent paper Vidyasagar V. (2021) identified, in women diagnosed with aerobic vaginitis (29–35 years), coagulase-negative Staphylococci growth in 50% cases, and in 25% Streptococci and Klebsiella [ 8 ]. S. aureus was the most abundant isolated pathogen for Nahar D et al (41.07%), Tansarli et al (41.7%) and Zarbo et al (27.9%) [ 12 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An accurate microbiological diagnosis allows the antibiotic sensitivity profiles of aerobic vaginal pathogens to be identified for rapid recovery and prevention of complications. Several studies report that the incidence of aerobic vaginitis ranges from 5 to 80%, widely variable as determined by socio-demographic factors, such as ethnicity, geographic location and socio-economic status [ 8 ]. The worldwide problem of aerobic vaginitis is strongly linked to the emergence of antimicrobial resistance (AMR).…”
Section: Introductionmentioning
confidence: 99%